2018
DOI: 10.24820/ark.5550190.p010.159
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of the antibacterial, antioxidant activities of novel functionalized thiazole and bis(thiazol-5-yl)methane derivatives

Abstract: Novel functionalized thiazoles were prepared by the Hantzsch reaction from 3-[(4hydroxyphenyl)carbamothioylamino]-2-methylpropanoic acid and the corresponding α-halocarbonyl compounds in good yields. A series of chemical transformations of the obtained products were carried out, and new functionalized thiazole derivatives with aliphatic, aromatic and heterocyclic substituents were synthesized. 4-Phenyl-substituted N-(4-hydroxyphenyl)-N-carboxyalkylaminothiazoles were used as precursors for the synthesis of bis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…The structure of compound 9 was also confirmed by further 1 H NMR spectroscopic analysis. The spectrum contains a methyl group singlet at 3.76 ppm, a CH-proton singlet at 6.61 ppm, and two broadened amino group singlets at 7.58 and 8.59 ppm.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…The structure of compound 9 was also confirmed by further 1 H NMR spectroscopic analysis. The spectrum contains a methyl group singlet at 3.76 ppm, a CH-proton singlet at 6.61 ppm, and two broadened amino group singlets at 7.58 and 8.59 ppm.…”
Section: Resultsmentioning
confidence: 64%
“…Among the derivatives of 1,3-thiazole, compounds have been found that have antioxidant 1 , antifungal [2][3] , antitumor, [3][4][5] antiproliferative, 6 and antibacterial, 1-3.7-9 properties including those effective against bacterial biofilms. [10][11] Thieno [2,3-d]thiazole-6-carboxylic acid derivatives are potential inducers of systemic resistance in plants.…”
Section: Introductionmentioning
confidence: 99%
“…=218-220 0 Ñ, I×,  cì -1 : 3450, 3364 (NÍ 2 ); 3325(NÍ); 1683, 1550(Ñ=Î). 1 Ðåçóëüòàòè òà îáãîâîðåííÿ Äî öüîãî ÷àñó ñèíòåçè ãåòåðîöèêë³â íà îñ-íîâ³ 1,4-íàôòîõ³íîíó âèêîíóâàëèñü ç³ ñòîðîíè áåíçîëüíîãî öèêëó [5][6][7]. Ââåäåííÿ NÍ 2 -ãðóïè â 7-÷è 6-ïîëîaeåííÿ íàôòîõ³íîíó äàëî ìîae-ëèâ³ñòü ñèíòåçó ð³çíîìàí³òíèõ ãåòåðîöèêë³â ç³ ñòîðîíè áåíçîëüíîãî öèêëó [8].…”
Section: 7-äèõëîðî-6-(25-äèìåòèë-1í-ï³ðîë-1-³ë)-3-ìîðôîë³í-4-³ë-í³unclassified
“…Profound biological activity of azole derivatives makes them as attractive building blocks to develop novel antimicrobial candidates for the further pre-clinical development [ 55 , 56 , 57 , 58 , 59 , 60 ]. In this paper we describe the synthesis and in vitro antimicrobial activity characterization of novel thiazole derivatives bearing N-acyl hydrazone, pyrrole, pyrazole, and triazole.…”
Section: Introductionmentioning
confidence: 99%